2015
DOI: 10.1007/s10900-015-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Body Mass Index, Sugar Sweetened Beverage Intake and Time Spent in Physical Activity of American Indian Children in Oklahoma

Abstract: American Indian (AI) children have a combined overweight and obesity prevalence of 53%. Behaviors that contribute to obesity, such as sugar sweetened beverage (SSB) intake and time spent in physical activity (PA), have been poorly explored in this population. The purpose of this study is to report body mass index (BMI), SSB intake, and time spent in PA of 7-to-13-year-old AI children who reside in rural and urban areas in Oklahoma. Cross-sectional survey study. Self-reported SSB intake in the last month, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Additionally, 71% of participants in our study reported low physical activity, consistent with other studies that have reported that most AI adults, and more than three quarters of AI youth, do not meet minimum public health recommendations for physical activity [27, 28], even though some evidence suggests that AIs engage in physical activity at higher rates than other racial/ethnic groups [29]. Finally, 25% of individuals we surveyed reported using tobacco.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, 71% of participants in our study reported low physical activity, consistent with other studies that have reported that most AI adults, and more than three quarters of AI youth, do not meet minimum public health recommendations for physical activity [27, 28], even though some evidence suggests that AIs engage in physical activity at higher rates than other racial/ethnic groups [29]. Finally, 25% of individuals we surveyed reported using tobacco.…”
Section: Discussionsupporting
confidence: 86%
“…The present study demonstrated that the percentage of normal body weight among participants who did not add vegetable or meat gravy to their rice was significantly higher than that among participants who occasionally or always added vegetable or meat gravy to their rice. Previous studies have echoed this idea that sugar and oil intake is associated with an increased risk for overweight and obesity [30,31]. One longitudinal study also investigated childhood dietary patterns and their association with childhood overweight/obesity, and reported that promoting a diet rich in whole meal cereals may counteract overweight and obesity in children [32].…”
Section: Discussionmentioning
confidence: 99%
“…Only 20% to 27% of AI/AN adults are estimated to engage in regular physical activity . Data on AI children in Oklahoma show similar trends, with only 30% meeting the 2008 Physical Activity Guidelines for Americans …”
Section: Physical Activity In Ai/an Childrenmentioning
confidence: 99%
“…71,72 Data on AI children in Oklahoma show similar trends, with only 30% meeting the 2008 Physical Activity Guidelines for Americans. 73 A systematic literature review of physical activity levels among AI/AN and First Nations people found that 26.5% of children met World Health Organization or Canadian physical activity guidelines according to studies using self-reported data, while 45.7% of children met guidelines according to studies based on accelerometry or pedometry, although selfreporting in children may be less reliable. 74 Other research shows that AI/AN children who do not participate in team sports, rarely engage in physical activity, and perform poorly on fitness tests have a higher risk of obesity.…”
Section: Physical Activity In Ai/an Childrenmentioning
confidence: 99%